Motivation to oral expression in the 17 de Julio Educational Unit - Tapia Cevallos, Jaime Rodrigo; Taramuel Obando, Héctor Darío; Mina Ortega, Marcelo René; Salazar Salazar , Amparo Andrea (Tierra Infinita, 2024)
The importance of oral expression in the educational field, highlighting how public speaking can generate physiological and psychological stress in individuals. It is highlighted that through practice and the development of appropriate techniques, drawbacks when speaking in public can become strengths. The relevance of motivation, both intrinsic and extrinsic, is emphasized in the development of oral expression, based on self-knowledge and personal reflection. The implementation of self-knowledge workshops is mentioned as a strategy to improve students' oral expression, as well as participation in debates on relevant topics to encourage active participation and quality of argumentation. The importance of motivation in the oral expression process is highlighted, since it drives the actions of individuals and can influence their attitude and participation in communicative activities. In summary, the document highlights the importance of practice, motivation, self-knowledge and active participation in the development of oral expression in students, offering recommendations and strategies to improve this communicative skill in the educational field.
Keywords: Motivation; oral expression; stimulation; self-knowledge; strategies